Grotowski, Kantor y Mrożek: Tres itinerarios del teatro polaco en América Latina - Dimeo, Carlos (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2022)
The central core of this article aims to theorise about the process of theatrical transitions, specifically based on the part dedicated to the “transitions” of Polish theatre in Latin America. The development of the theory begins with a fundamental question: how did and does Polish theatre influence and influence Latin American theatre, and at the same time, what were its points of departure, its routes, its journeys? In this work, the category of “transition” raises several problems. It is defined in two ways, it is both an episteme and a category. Consequently, this research framework will offer to analyse, present and show which are the axes of transition that have marked the perspective of sense and meaning in Latin American theatricality from the 1960s onwards, taking as the object of study for this purpose the influences of Grotowski, Kantor and Mrożek. If so, these broad time frames would predict an “ultimate destiny” that remains to be discovered and that will “allow” us to cover long periods of time in the context of the proposed study. It is necessary to mention that the article will work on two categories of research, namely 1.- The axis present in Genealogy (Foucault): The pass, the transfers, the mechanisms of translation; 2.- On the axis of the theatrical epistemes that organise, reinterpret, distribute the discourses in their respective fields of action. Finally applying the Theory of Transitions, it will be possible to observe and study in detail the starting points, the “scenic routes” that these three creators had on the continent.